Moving from Access to Meaningful Participation through Outdoor Classroom Practices in Inclusive Early Childhood Education - Agung Prasetyo (Al-Qalam Institute, 2026)
Inclusive early childhood education should not stop at institutional access, as children with special educational needs also require learning environments that enable meaningful participation in daily classroom life. This study aims to synthesize illustrative access-oriented statistical evidence and classroom-based pedagogical evidence on outdoor learning practices in inclusive early childhood education. Using a descriptive-integrative approach based on secondary data and document-based synthesis, this study examined two complementary forms of evidence: statistical data on the distribution of early childhood students with special educational needs across different types of educational centers and pedagogical evidence on outdoor classroom practices in an inclusive early childhood setting. The illustrative statistical evidence from the 2013/2014 dataset shows that public centers recorded the highest proportion of early childhood students with special educational needs at 1.1%, followed by charter education at 0.6% and private non-subsidized education at 0.2%. Meanwhile, the classroom-based evidence indicates that outdoor classroom practices can support inclusion through natural learning media, fun and play-based learning, and daily cognitive-behavioral assessment. The synthesis suggests that inclusive early childhood education should move from administrative inclusion toward participatory inclusion, where access is translated into adaptive outdoor pedagogy, child-centered assessment, teacher readiness, and responsive learning environments. This study contributes to inclusive education discourse by showing that access data need to be interpreted together with classroom-level practices to understand whether children with special educational needs are not only enrolled, but also meaningfully engaged in learning.